PEMASANGAN ALAT PEMADAM API RINGAN DI PT E-T-A INDONESIA - Faisal Lestaluhu; Indriati Paskarini (Universitas Airlangga, 2019)
Fire extinguisher is one of active protection that effectively used to extinguish at the incipient of the fire. Installation of fire extinguisher were urgently needed to support a company’s efforts to control fire. The purpose of this study was to learn about appropriate the installation of fire extinguisher in PT. E-T-A Indonesia with Peraturan Menteri Tenaga Kerja dan Transmigrasi No. PER.04/MEN/1980. This study was a descriptive research. The primary data obtained by interviews, observation and measurements in the field. Data collected were analyzed descriptively using narration and tabulation. In addition, secondary data were also obtained from documents at PT. E-T-A Indonesia. The research result was the company did not have a spesific policy but the installation of fire extinguisher had been applicated. PT. E-T-A Indonesia had 36 pieces of fire extinguisher with 23 dry chemical powder type and 13 carbon dioxide (CO2) type, which has capacity 3–6 kgs. Implementation of the fire extinguisher insatallation was not accordance with requirements in terms by the distance of each fire extinguisher, fire extinguisher mounting height, and sign to declare fire extinguisher. Based on the research result, it was recommended that the company to make specific policy about the installation of the fire extinguisher. Therefore, the implementation of installation of the fire extinguisher at PT. E-T-A Indonesia more appropriate with Peraturan Menteri Tenaga Kerja dan Transmigrasi No. PER.04/MEN/1980.Keywords: installation, fire, fire extinguisher